2019
DOI: 10.1177/1745691619863049
|View full text |Cite
|
Sign up to set email alerts
|

The Misperception of Racial Economic Inequality

Abstract: Racial economic inequality is a foundational feature of the United States, yet many Americans appear oblivious to it. In the present work we consider the psychology underlying this collective willful ignorance. Drawing on prior research and new evidence from a nationally representative sample of adults ( N = 1,008), we offer compelling evidence that Americans vastly underestimate racial economic inequality, especially the racial wealth gap. In particular, respondents thought that the Black–White wealth gap was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
168
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 170 publications
(209 citation statements)
references
References 102 publications
(154 reference statements)
10
168
1
Order By: Relevance
“…Specifically, this pattern is consistent with the possibility that being asked to consider inequality in the past and in the present heightens the salience of narratives of societal racial progress; namely, that racial equality is linearly increasing over the passage of time (Hur & Ruttan, 2019;Kraus et al, 2019; Richeson, 2020)-a belief not activated when only considering the present state of society. That narratives of racial progress inform perceptions of racial inequality is something that we and others have theorized (Bell, 1987;DeBell, 2017;Eibach & Ehrlinger, 2006;Kraus et al, 2019;Seamster & Ray, 2018). The present investigation also furthers the aims of related research that considers how highlighting the salience of racial inequality and racism across time can activate beliefs in societal progress (see Onyeador et al, 2020).…”
Section: Framing Context and The Perception Of Black-white Wealth Isupporting
confidence: 65%
See 4 more Smart Citations
“…Specifically, this pattern is consistent with the possibility that being asked to consider inequality in the past and in the present heightens the salience of narratives of societal racial progress; namely, that racial equality is linearly increasing over the passage of time (Hur & Ruttan, 2019;Kraus et al, 2019; Richeson, 2020)-a belief not activated when only considering the present state of society. That narratives of racial progress inform perceptions of racial inequality is something that we and others have theorized (Bell, 1987;DeBell, 2017;Eibach & Ehrlinger, 2006;Kraus et al, 2019;Seamster & Ray, 2018). The present investigation also furthers the aims of related research that considers how highlighting the salience of racial inequality and racism across time can activate beliefs in societal progress (see Onyeador et al, 2020).…”
Section: Framing Context and The Perception Of Black-white Wealth Isupporting
confidence: 65%
“…As depicted in Figure 1, our past research (both published and unpublished data) has reliably found that when compared to the actual amount of Black-White wealth equality estimated based on the SCF or SIPP, respondents significantly overestimate Black-White wealth equality (Kraus et al, 2019(Kraus et al, , 2017. Nevertheless, there is also evidence in our past work suggesting that the context in which we solicit estimates of Black-White economic equality may contribute to the degree that people overestimate it.…”
Section: Framing Context and The Perception Of Black-white Wealth Imentioning
confidence: 62%
See 3 more Smart Citations